The species intermediate between Hieracium petrovae and H. olympicum (Asteraceae): a treatment of H. kritschimanum and description of a new species from Greece - Szeląg, Zbigniew; Vladimirov, Vladimir (Phytotaxa, 2019)
Hieracium kritschimanum is neotypified with specimens collected in the type locality in Bulgaria. The etymology and original spelling of the species epithet of H. kritschimanum are clarified. Hieracium pangaeum, which combines the morphological features of H. petrovae and H. olympicum, is described from northern Greece. Both species are illustrated with photos of herbarium specimens. A distribution map of H. petrovae, including its first records from Greece, is provided.